Improved SnO2 Electron Transport Layers Solution‐Deposited at Near Room Temperature for Rigid or Flexible Perovskite Solar Cells with High Efficiencies. Issue 26 (28th May 2019) - Dong, Qingshun; Li, Jiangwei; Shi, Yantao; Chen, Min; Ono, Luis K.; Zhou, Ke; Zhang, Chunyang; Qi, Yabing; Zhou, Yuanyuan; Padture, Nitin P.; Wang, Liduo
Abstract: Electron transport layer (ETL) is a functional layer of great significance for boosting the power conversion efficiency (PCE) of perovskite solar cells (PSCs). To date, it is still a challenge to simultaneously reduce the surface defects and improve the crystallinity in ETLs during their low‐temperature processing. Here, a novel strategy for the mediation of in situ regrowth of SnO2 nanocrystal ETLs is reported: introduction of controlled trace amounts of surface absorbed water on the fluorinated tin oxide (FTO) or indium–tin oxide (ITO) surfaces of the substrates using ultraviolet ozone (UVO) pretreatment. The optimum amount of adsorbed water plays a key role in balancing the hydrolysis–condensation reactions during the structural evolution of SnO2 thin films. This new approach results in a full‐coverage SnO2 ETL with a desirable morphology and crystallinity for superior optical and electrical properties, as compared to the control SnO2 ETL without the UVO pretreatment. Finally, the rigid and flexible PSC devices based on the new SnO2 ETLs yield high PCEs of up to 20.5% and 17.5%, respectively. Abstract : A novel strategy is reported where control over the surface‐adsorbed water on a transparent conducting oxide substrate is used to mediate the in situ nanocrystalline regrowth of a SnO2 electron transport layer (ETL) at near room temperature. The new ETL is key to achieving a high power conversion efficiency of 20.5% and 17.5% in rigid and flexible perovskite solar cells, respectively.